Vindobona Common Ware production: what the excavation (Rennweg 44) of material from the civilian settlement adds to current research - Chinelli, Rita (Rei Cretariae Romanae Fautorum Acta, 2022)
This paper introduces an overview of current knowledge about common ware (oxidised ware) production at Vindobona (Pannonia): kiln distribution within the area and the presence of wasters are indicators of such activity. The new contribution results from the almost concluded project about the excavation at Rennweg 44. Archaeometric analyses made possible the description and interpretation of a wide fabric collection related to all pottery forms, which will serve as reference basis for future material. The analysis of some possible potters’ tools, hitherto not found at Vindobona and generally very rare, will allow the easier identification of other workshops. In the local pottery the link with Italy can be found in the preference for imitations of terra sigillata, of metal and glass forms and for the “legionary” style. A large part of the production consists of provincial forms with parallels in Pannonia, sometimes modified in details by local tastes. This resulting pattern placed Vindobona in the production program already estabilished for the castra on the Danubian limes.